Jernalderofferfund i Valmose ved Rislev - Ferdinand, Johs. & Klaus (Kuml, 1961)
The lron Age Find from Valmose near Rislev. During the intense peat digging of the last war, the above mentioned peat-bed find came to light. It was excavated in 1941-44 in Valmosen near Rislev, about 6 km N. of Næstved in South Zealand 1). The excavations were made in the middle of the long and narrow bog (at this point only 50 m wide) which has been formed about a stream (fig. 2). 60 sq. m were investigated and areas without finds were arrived at in all directions except to the east; the place of sacrifice can, thus, hardly have extended further. (cf. fig. 3). The find consists of a limited number of artifacts (fig. 3 nos 1-11), a considerable collection of bones of domestic animals numbering at least 29 individuals, the almost complete skeletons of 2 human beings and a few other human bones. There were, besides, 2 other categories of finds which must he attributed to the work of human hands, consisting partly of branches and sticks hearing hacking marks and partly of the occurrence of stones. All of the above mentioned categories were found within most of the excavation area (figs. 3, 4 and 6) and at considerably varying levels (fig. 8). There could be no question of a clear stratigraphy as at the time of deposition the natural surroundings about the place of sacrifice would have been an alder and willow swamp with lush meadow vegetation on the land side and with a reed swamp towards the open shallow water (vid. Troels-Smith, p. 91). By means of bone determination, it is usually possible to ascertain what bones and parts of bones have belonged to the same individual and here, together with comparisons with the other finds, important information concerning the disturbances and redepositions of the area can he obtained. The greatest disturbances were found to have occurred in the western and north-western parts (cf figs 12, 13 and 14) in the proximity of the open water; the least disturbed conditions were found in the southerly and central-easterly parts (vid. figs 7, 9 10 and 15). The disturbances can he attributed to floods and to possible winter ice-drifts. In the north-westerly part, they may also have been due to a partial erosion of the original shore deposit. Finally, it must he added that it is not known whether the original swamp surface was even or pocketed. No traces of burying were discovered. Considerable quantities of branches and twigs, together with some isolated logs, were found all over the excavation area. These were remarkable for the traces that they bore of hacking and felling (cf. fig. 5), and for the fact that, by and large, there appeared to be a directly proportional relation between the number of branches marked by human agency and the total number of branches in the various areas (cf. fig. 3, where the Jack of branches etc. in the central part is chiefly due to the fact that these conditions were not so fully recorded here). It is, therefore, our opinion that the presence of these branches must, predominantly, be attributed to humans and must be taken to have been a covering up of the deposits. A comparison of the plans figs 3 and 4, shows a considerable agreement in the horizontal distribution of stones, severed branches, bones and artifacts. It can most clearly be seen in the outer areas towards the west, the north-west and the south. It seems to be apparent here that the stones and branches extend. beyond the actual site of the votive offerings by from 1/2 to 1 metre. A consideration of the vertical distribution of the above mentioned categories can but confirm our supposition of a covering-over. In the most southerly part: Ø. 5, 5-7, 5; N. 0, 6-1,6) the vertical section, measured from the surface of the sward, was distributed as follows: Ox-hones in a heap (Ox V) . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . 72-85 cm depth Horse-feet (Horse IX) . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .68-85 cm depth Pig-jaws, pieces of. . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . . .106-11 cm depth Severed branches (7 in all) . . . . . at depths of 50, 62, 68, 78, 83, 108 and 112 cm Stones (10 in all) . . . . . . at depths of 60. 62, 64, 67, 67, 68, 74, 75, 76 and 78 cm It thus appears (as also from the tables p. 53) that the branches and stones are, on the whole, sited at a higher level than the skeletal finds. To this must he added the fact that, of all the 8-900 bones of which the find was composed, only one bears traces of having been gnawed by a dog. It must follow that a covering-up is the most likely explanation. A corresponding wattled covering has been found over peat-bed corpses 5) and, possibly, in the Bukkerup find 6); it is, however, also conceivable that the branches have served as a platform from which further votive offerings have been made (cf. Karingsjon 4). About 125 stones have been catalogued in this find. The majority were smaller than a hand in size. About 20 were of a size that may conveniently be described as "stepping stones", without their use as such being either obvious or provable (the largest stone was 40 X 18 X 18 cm). The stones were found distributed over the excavation area at various depths (cf. figs 4 and 8). They seem clearly to have formed a part of the "cover material" although their purpose is not plain. The larger stones may have helped to secure the animal remains etc. that were deposited, or they may have weighed the covering branches down, for the smaller stones were scattered far too thinly for this purpose. It may be necessary to attach some ritual significance to their presence comparable with the "ritual throws" known in Northern folk culture and discovered also in many other peat-bed votive finds 5) & 6). The Domestic Animals The Horse. The largest number of animals found were horses, and, archeologically, they attract most attention. With one exception, the deposits consist of only the bones of the head, the feet and the tail. A more or less complete collection of bones from these parts of altogether 11 horses were found. Fig. 7 shows the position of each; the bones were as follows: Hest I: Head, 4 Feet, 2 Stylohyoid Bones (rather fragmentary) lying close together. Hest II: Head, 4 Feet, 2 Stylohyoid Bones (middle pieces only) and 5 Caudal Vertebrae, lying close together. The foot bones of I and II lay in a heap. Hest III: Head and 4 Feet, rather scattered. Hest IV: Head, 4 Feet and 2 Caudal Vertebrae, rather scattered (vid. fig. 12). Hest V: Head, 4 Feet and 2 Stylohyoid Bones (well preserved). Very scattered and Hest VI: partly mixed with Human Being I (cf. figs 6 and 7; vid. figs 13 and 14). Head, 4 Feet, 1 middle part of the Stylohyoid Bone and 10 Caudal Vertebrae lying between the Lower Jaw Bones. Everything lying close together and undisturbed (vid. figs 9 and 10). Hest VIII: 4 Feet lying close together. Hest VIII-IX: 4 + 4 Feet and 15 Caudal Vertebrae derived from various individuals (11 from 1 individual) all lying close together. Hest X: 6 Foot Bones of the left back leg and 1 of a foreleg and, possibly 2 Caudal Vertebrae extremely scattered. (The distribution coincides in part with Hest V, vid. Fig. 7). Hest XI: 4 Feet, lying close and undisturbed (vid. fig. 15). Hest “XII”: Fragmentary and marrow split bones of several individuals, undoubtedly the I-XI mentioned above. No head parts, feet nor tail. All very scattered. In other words, the head had been deposited together with the 4 feet in 6 cases. In 3, parts of the tail were found besides. In no case was the head found lying alone. In 4 cases, only the 4 feet of each individual were found lying in a heap. In 1 case there were 15 caudal vertebrae besides. The foot bones and the tail bones were found scattered in 1 case only (Hest X) and it could not be determined whether they had originally been deposited together. As regards the 10 (11) horses, there can be no doubt that these parts of the bodies had been deposited in the bog as a votive offering or the like. The heads had all been crushed with a blunt object, presumably at the slaughtering, the jaw bones were whole and the rows of teeth well preserved. Parts of the hyoid bone, the stylohyoid bone (os stylohyale), were found whole or in part in 4 cases (Hest I, II, V and VI). In Hest III and IV no hyoid bone was found, in VI only the middle part of the right horn was found. It is most probable that the tongue had been removed before the head was deposited; in no case was the central part (basihyale) discovered. It is true that no cutting marks appear on the stylohyoid bones but, according to U. Møhl, the tongue may well be removed without marks appearing on the hyoid bones as the various parts are connected by cartilage (cf. oxen and sheep). In 1 case (Hest VI) 10 caudal vertebrae were found lying between the lower jaw bones from which it must be supposed that the severed tail less the 4 upper caudal vertebrae, had been thrust into the horse’s mouth and taken the place of the tongue. A larger or smaller number of the caudal vertebrae of at least 5 horses was found, but in no case were the 4 upper caudal vertebrae discovered. This may possibly be due to two conditions, that the fleshy tail-root had been eaten and that the lower part of the tail had been severed when the animal had been flayed. The feet had all been severed in the middle of the carpal or tarsal bones, in the latter case below the talus and calcaneum which were not found in any instance. There were distinct cutting marks from the dismemberment which had been executed with care and, with the exception of a single slip, the feet bore no trace of violence, still less of any kind of crushing or splitting. Judging from the least disturbed of the finds, the feet seem to have been deposited whole, i. e. with, at any rate, the tendons attached, and, possibly, with the skin on also. It is not improbable that the dismembering was done together with the flaying, so that the feet along with the head and the tail remained in the hide. However, the part played by the hide, in sacrificial rites, is obscure. It calls for special caution that the caudal vertebrae are not complete in number while the bones of the feet are, also that the feet have been deposited alone (in part in company with the caudal vartebrae) but without the head. These are not incomplete finds; the conditions under which the finds were made preclude the possibility of the heads also having been deposited in these cases. Whilst the head, feet and tail must be presumed to have been subjected to a treatment unknown to us before they were laid into the swamp, horse "XII" demonstrates clearly that the other parts of the horse had not enjoyed any special "protection". They had been consumed and then, more or less by chance, some of the bones have landed on the place of sacrifice after the meal was over. The special treatment that has been accorded to the horses in this find applies to all of them. There were animals of both sexes, young as well as old. The Ox. The remains of at least 7 animals were found, predominantly remnants of meals. The bones of the various individuals lay fairly close together, and only slightly mixed with others, hence it may be deduced that they were deposited separately and probably, in succession. The heaps of ox bones that lay closest together (III and IV) were found at approximately the same depths (vid. fig. 8) as, and in fairly close proximity to, Hest VII and XI, respectively, giving the impression that ox and horse can have been deposited side by side at the same time. The part played by the oxen is not easily interpreted. This is at once apparent from the very different treatment accorded to the heads and the bones of the legs: partly from the fact that whole leg-bones have been deposited with the head (ox I), partly from the heaps of marrow split and splintered remnants of heads and limbs (oxen IV and V).-Great zeal in the exploitation of everything edible is evinced by the total rending of skulls, vertebrae and leg bones etc. (oxen III, IV (vid figs 17 and 18), V and VI), and especially remarkable is the severance of heads IV and V. A ritual act may be guessed at here. Oxen I and II distinguish themselves from the other remains. Ox I, of which whole bones of the head, neck and legs were found, had suffered very little violence. There was no marrow splitting, but, on the other hand, marks caused by the quartering seem to indicate that these are, none the less, the remains of a meal, at any rate, in part. The butchering method employed is obscure. Any method is conceivable, ranging from the neck incision suggested by the cutting marks on the occipital condyle to the possibility of its having been a dead and not a slaughtered animal. It is, however, worth emphasizing that the find consisted substantially of the head and legs (feet). All that was found of ox II was the head with the forehead crushed and the core of the horns missing. The butchering method seems to have been similar to that used on the horses. It is conceivable that oxen IV and V were killed in the same way; the cores of the horns were missing in these as well as in all the other oxen, and they may, presumably, have been removed during the flaying. As the central parts of the hyoid bone were missing, the tongue may be supposed to have been cut out. The feet seem to have had some special significance, but rules are hard to deduce as no strict practice was observed, which can be seen from the fact that the carpal and tarsal bones of oxen IV and V were marrow split, while some special connection seems all the same to have existed between the head and feet. In the cases where the head. or the remains of the head, were present (ox II excepted) the feet were present as well (oxen I, IV and V), and, conversely, where the head was missing the feet were missing also (III and VI). The connection is, however, not at all clear, for in 2 of the 3 confirmatory cases (I and V) parts of the rest of the leg-bones were also found. It has been mentioned above that "normally" the feet of the horses and oxen were severed below the talus and calcaneum so that these bones were not included in the dismembered parts. A talus, bearing cutting marks, belonging to ox III was found, but the rest of the feet were missing. The presence of a single talus, the only one of the bones of the feet of oxen VI and VII that was found, leads to the supposition that the feet of these animals may have been severed also. It may, therefore, be presumed that in butchering an ox, it was the common thing to cut off the fee" (and the cores of the horns?) at the same time as the animal was flayed. The complete absence of caudal vertebrae may also have a connection with the flaying. But why have they not ended in the bog? Can it be because (amongst other reasons) an ox hide was not a votive object? The oxen found were both young and old and of both sexes. The Dog. The find included the skeletons of 3 dogs, 2 of them (Il and III) fairly complete, and of the third (I) there was the skull and a thigh bone only. In the last case, it is not impossible that the dog had been deposited on a wooden board (fig. 3, no. 9). Nothing can be said with certainty of the cause of death of any of the dogs. The may, conceivably, have been hanged, which is a wide-spread method of destroying dogs in northern districts (Eskimos, Lapps etc.). One thing remains certain-there is nothing to suggest that the dogs had been eaten. The Sheep. The remains of 5 animals were found, 2 old, 1 young and 2 lambs, but there was a representative collection of bones. from one animal only (Sheep I). Of this animal the head and the bones of the 4 legs were found almost complete. The skull had been crushed by a deadly blow on the forehead and the cores of the horns had been broken off and severed at the base. The leg bones were whole but it appears from U. Møhl’s scrupulous examination that the presence of cutting marks proves that the animal was cut up at the joints and that lumps of meat had been cut off the bones. The other sheep remains confirm the main impression that only the head and leg bones were deposited. There seems no doubt that the tongues of the sheep had also been cut out beforehand. The Pig. The chance and scattered bones of at least 3 pigs were found. These were hacked and broken and were clearly the remains of meals that had found their way into the bog. Human Beings. Widely spread over the excavation area were found bones belonging to at least 4 humans (vid. fig. 5). There were the fairly complete skeletons of 2 women (I and Il), parts of the skeleton of a child (III), a talus and 2 teeth. From the positions of these finds it is clear that the skeletal parts have floated about considerably. Human I lay towards the north where the bones were most numerous and the depths on the whole, greatest. They were mixed up with the bones of Hest V (vid. fig. 14, cf. figs 6 and 13). A distinction between the way the human and the animal remains have been deposited does not seem to be called for. The human bones have been scrupulously examined for traces of cutting marks or other signs of violence but without result. The Cultural Relics and their Dating. The few artefacts discovered were found in the rich, northern part of the original peat-bog (vid. fig. 3). They were scattered among the remains of ox I and sheep II and to the west of and close to dog I and horses I and II. A thin-walled, slightly crushed earthenware vessel was found at a depth of 77 cm. Professor D. J. Becker has kindly expressed the following opinion of this vessel: "In both form and ornamentation this vessel seems best to belong to the later part of the Early Roman lron Age (4th cent. A.D.), despite the fact that ....... no exact parallel is known." He refers also to "a rather similar vessel" from a grave in Källby, Skåne, Sweden 9). Klindt-Jensen writes of this same vessel as follows: "This type of vessel belongs to the end of the Roman lron Age and to the era of the Great Migration" 10). The vessel, and with it, the find, must hence be dated to c. 4-5th cent. A.D. Fig. 3, no. 2 is a potsherd from a large, thick-walled, coarse vessel. It lay at a depth of 87 cm. 2 smaller sherds, lying at 85 cm (figs 3, nos 3 and 4) are parts of the same vessel. 4 wooden objects lay, not far from each other, to the east of the vessel. Fig. 3, no. 9 is a part (in 3 pieces) of a wooden board, about 2 cm thick, the diameter of which has been about 20 cm. This board lay, as has been mentioned already, close to dog 1 and about 80 cm deep in the ground. Fig. 3, no. 10 is 2 pieces of a "tethering stake" of hazel-wood, which lay at a depth of from 85- 90 cm. The pointed end (vid. fig. 20) is 13 cm long, the other end measures 10 cm. Both show distinct cutting surfaces. In shape and size this stake is reminiscent of the tethering stake notched for fastening a rope, found among the sacrificial finds in Bukkerup Bog on Fyn from the Early Roman Period 12). It must be pointed out that the notch for fastening is lacking in the Rislev piece. Incidentally, the combination of earthenware vessels, potsherds, tethering stake and animal bones accords very well with the Bukkerup find8). Fig. 3, no. 11 is 2 pieces, about 20 cm long, of a square cut peg of beech-wood, the use of which is uncertain, (depth 10 9-17 cm). The 3 remaining artefacts were found in more scattered positions. A spindle-whorl (fig. 3 no. 5; fig. 22) lay fairly near to human II at a depth of 85 cm. It is of fine grained sand stone, well rounded and flattened, 5.2-5.4 cm in diameter and c. 0.95 cm in thickness. Similar stones are known from grave finds of the Early Germanic Period and it may well be dated to the 4-5th cent. A.D.12). The significance of the spindle-whorl is not clear. Has it just been dropped? Or has it landed in the bog as a result of a "ritual throw" like the other stones? It is ’tempting to set it in connection with the skeleton of the woman lying nearby, which, however, lay a good deal deeper. Fig. 3, no. 6 is the fashioned rib of an ox (vid. fig. 21), which lay at a depth of 85 cm. It is 15.6 cm long and 0.9 cm thick. The surface on both sides is worn smooth and finely scratched. The thin side has been cut to a knife-like edge and the upper end (with secondary notches) is slanted off. It may have been a tanner’s smoothing piece, or the shed of a braidloom 13), but it may, most probably, be an implement for burnishing earthenware. Whatever it is it must be assumed to be a woman’s implement and as such, it is remarkable to find this too, in such close proximity to the skeleton of a woman (human being I). Lastly we have in fig. 3 no. 7 a little profiled edged sherd found at a depth of 123 cm. It may well belong to the 4-5th cent. A.D. The Character of the Find. The Rislev find is clearly a votive offering, no other explanation covering its uniform stamp and the scope of its contents. Through the artefacts we have been able to date the find to approximately 4-5 cent. A.D. Does this apply to the entire find? The uncertain stratigraphy makes a definite decision difficult. A consideration of the fairly undisturbed heaps of bones of horses VIII-IX and horse XI, which lay, respectively, deepest and highest in the peat, and a consideration of how individual animals lying in close proximity to each other in the "quieter" parts of the excavation area are placed at different levels (for ex. dog II, horses VIII-IX, ox I etc.), makes it reasonable to suppose that we have here a series of depositions following one another over a fairly long period. Sacrificial rites recurring yearly, or more possibly, after several years may have been performed in the swamp, as it then was. With regard to the human skeletons, it has been seen that the branch covering, and the stones belong as much to them as to the animal remains. In depth these 2 groups of finds overlap each other (vid. fig. 8), but the general impression is, all the same, that the human remains had been placed at a somewhat greater depth than the majority of the animal bones. The main impression is, however, to put it briefly, but without real certainty, that the human and animal deposits must be taken together as links in a chain of sacrifices in which humans appear among the earliest, and, as a detail, sheep I and dog III among the latest. Votive offerings from peat-bogs in which human and animal bones appear are known from the Late Bronze Age 14, from some of the more warlike peat-bog votive offerings of the Iron Age 15) and from a single "peaceful" offering from the Roman Period 16, while the material has only received scant attention in the literature. A comparison with peat-bog corpses which are known throughout the whole of the Early Iron Age 17), brings out several points in common: the appearance of pottery vessels, boulders, branches and fashioned switches along with the corpses, also the occurrence of several corpses in the same bog and finally, the fact that about half of the known corpses are of women 18) & 19). The Rislev women can, thus, be taken to be peat-bog corpses. In this connection, it may be mentioned that the branch covering, the sticks and stones, may conceivably, be a measure against ghosts 23). Apart from this the human finds in Rislev differ from other peat-bog corpses in that their connection with the other offerings in the bog gives them a wider significance. The animal sacrifices stand out more clearly than the human. Definite rules seem to have been followed, apart from the chance appearance of the pigs’ bones. The dog, which has probably stood in a specially intimate relationship to humans, has usually been deposited whole. Otherwise it is a common feature, apart from the case of some of the oxen, that whole bones of limbs (or feet) have been deposited together with the head (and parts of the tail). This is a combination of circumstances for which there is a tradition in this country, and not only from the Early Iron Age and Neolithic Period; but which must, possibly, also be considered in relation to the Palaeolithic head- and leg-bone sacrifices and to the sacrifices made by hunters and nomads in the northerly regions of the Old World in our own times24). In Rislev this sort of sacrifice is seen in its purest form in the case of the sheep. Close parallels to Rislev can be sought in the groups of finds known as "mosepotter" 25) -"bog-pots"; the Bukkerup find is one of the few published finds in which these are described in detail -8). Like the Rislev find, whole leg bones, pottery vessels and tethering stakes had been deposited, but it was unlike the Rislev find in that there were no skulls at all. The Bukkerup find consisted chiefly of the oxen, the pottery vessels etc. The Rislev find was composed of a far greater variety of domestic animals (and also of humans) with the horse as the most important. The Bukkerup find is dated to the 1st cent. A.D., the Rislev to the 4-5th cent. A.D. We are thus, with all due reservations to the paucity of the material confronted with a clear change of custom in these centuries. The horse appears the most important votive animal and at the same time the ancient whole leg offering has become reduced to embrace the feet alone. The strength of this new custom is felt in the hesitation as to the manner in which the oxen have been sacrificed. Both whole legs and feet were deposited and there was, moreover, some special, but not entirely fathomable, connection between the head and the feet. Parallels to the votive offering of horses in the Rislev find can be found in material from this country in the pit of Sorte Muld, Bornholm, from the 4th cent. A.D. and, possibly, from a couple of burial places 31). Beyond these the finding of the head and feet bones of horses is known from 4 undated peat-bog finds scattered over the country 32). KlindtJensen has in several of his writings 30) attempted an interpretation of these special offerings. On the basis of the finds just referred to he notes that this votive custom appeared at the end of the Roman Period and was apparently widely spread, but had been discontinued by the time of the Viking Period when the skeletons of whole horses were included in the graves 34). An explanation of this new votive custom must be sought outside this country. KlindtJensen has succeeded in finding a number of striking foreign parallels, mostly derived from graves and from pits in connection with them and also from a bog votive offering find from Oberdorla 30) & 36), which ultimately is connected with influences and points of impact from the Central Asiatic horse riders of the South Russian Steppe districts 35). This statement seems convincing. In connection with the discovery of a long pole near the skull of a horse in Oberdorla, Thüringen, and bearing in mind the Central Asiatic votive custom of placing the horse’s hide with the bones of the head, feet and tail still attached on a pole so that the horse appeared to be springing up into the sky Klindt-Jensen suggests that something similar may have taken place in this country. With this end in view, U. Møhl examined the horses’ skulls minutely to see whether any traces of having been stuck on a pole could be discovered, unfortunately with negative result. But apart from this as has already been mentioned, it does seem as if the hide has also played a significant part in the votive rites and this supposition is strengthened by an appreciation of a connection between the offerings at Rislev and in Central Asia cf. fig. 23. The Rislev offerings have undoubtedly been made to gods or goddesses governing the fertility of the cattle and the growth of the crops and to gods who have aided mortals in the toil of daily life 40) & 41). The offerings can be classed in the group called. "pars pro toto" where a part was offered for the whole41). Similar ideas lie behind Snorre’s tale of Thor’s re-creation of his goats from the whole, gnawed off bones 42), and of Sæhrimnir, the immortal boar, which was daily butchered for Odin’s giants in Valhalla, and which grunted every morning anew, alive and unharmed 43). The votive offering site at Rislev must certainly be compared with the sacred groves described by Tacitus as the places of worship of the Southern Germans 45), in which ancient, native traditions thrived mixed up with oriental and other foreign influences 46). Johs. Ferdinand & Klaus Ferdinand